2007
DOI: 10.1080/07370010701429579
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Obesity and Childhood Obesity: Implications for Healthcare Providers

Abstract: The purpose of this critical appraisal was to assess the available literature on the association of maternal obesity as a risk factor for childhood obesity and to explore the implications for incorporating this evidence into practice. The increasing prevalence of childhood obesity, with its documented adverse health effects, is a critical public health threat in the United States and worldwide. Research studies have documented increased rates of childhood obesity associated with maternal obesity. Healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Ourresultsshowedapositiveassociationbetweenparental andchildweightstatus,afindingconsistentwithotherstudies [25,26].Therelationshipbetweenparentalandchildweight status is mediated by a number of factors, both genetic and environmental. Since we found a significant association beperday.Finally,therewasaclearassociationbetweenthenutritional status of children and their parents (p < 0.001 for both parents), as overweight and obese parents were more likely to have overweight and obese children than the nonoverweightmothersandfathers.…”
Section: Non-respondentssupporting
confidence: 70%
“…Ourresultsshowedapositiveassociationbetweenparental andchildweightstatus,afindingconsistentwithotherstudies [25,26].Therelationshipbetweenparentalandchildweight status is mediated by a number of factors, both genetic and environmental. Since we found a significant association beperday.Finally,therewasaclearassociationbetweenthenutritional status of children and their parents (p < 0.001 for both parents), as overweight and obese parents were more likely to have overweight and obese children than the nonoverweightmothersandfathers.…”
Section: Non-respondentssupporting
confidence: 70%
“…A variety of conditions are associated with obesity in women (including type 2 diabetes mellitus, CVD and breast cancer, among others) (2) that not only decrease their survival, but also compromise their current quality of life and reproductive health (3) . Moreover, maternal obesity is an important risk factor for childhood obesity (4) ; thus, obesity in women has a multiplicative detrimental effect.…”
Section: Obesity Weight Gain Women Latin Americamentioning
confidence: 99%
“…A variety of conditions are associated with obesity in women (including type 2 diabetes mellitus, CVD and breast cancer, among others) (2) that not only decrease their survival, but also compromise their current quality of life and reproductive health (3) . Moreover, maternal obesity is an important risk factor for childhood obesity (4) ; thus, obesity in women has a multiplicative detrimental effect.Chile, a post-transitional upper-middle-income Latin American country, has experienced a rapid epidemiological and nutritional transition (5) . The 2003 and 2010 National Health Surveys informed an obesity prevalence in women aged 25-44 years of 26?1 % and 28?3 %, respectively (6,7) .…”
mentioning
confidence: 99%
“…Arluk, Branch, Swain, and Dowling (2003) and Kimbro et al (2007) conducted studies that revealed maternal obesity as the strongest independent predictor of childhood obesity, and research by Salsberry and Reagan (2005) suggested that maternal prepregnancy obesity influences early childhood obesity, which is perpetuated as the child ages. Among low-income children, maternal obesity in early pregnancy (during the first trimester) more than doubles the risk of obesity at 2-4 years of age (Durand, Logan, & Carruth, 2007;Whitaker, 2004). Furthermore, children's birth weight is a predictor of being overweight or obese at three years of age (Kimbro et al, 2007), and obesity at one and two and a half years of age is predictive of obesity at five years of age (Huss, Ludvigsson, Enskär, & Ludvigsson, 2007).…”
mentioning
confidence: 96%
“…Although obesity has increased the risk of a number of chronic health conditions, diabetes is the most closely associated with obesity (Durand et al, 2007). Being overweight is a significant risk factor for type 2 diabetes (Fagot-Campagna, Saadinem, Flegal, & Beckles, 2000), and the incidence of diabetes has increased as has the prevalence of obesity, accounting for nearly 50% of new cases in pediatric diabetes in some areas of the country (Fagot-Campagna et al, 2000;.…”
mentioning
confidence: 99%